2020
DOI: 10.29023/alanyaakademik.646546
|View full text |Cite
|
Sign up to set email alerts
|

Market Integration of Sesame Seeds in South Asia

Abstract: The present research empirically determined the spatial price linkage of South-Asia exporting sesame seeds markets with the importing market using annual producer's price sourced from FAO database. The analytical techniques used to achieve the stated objective were descriptive and inferential statistics. The empirical findings showed that the selected markets were not autarkic as price information was efficiently transmitted across the geographical far apart markets. Furthermore, the traders effectively respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…A ceiling price tends to promote negative skewness while a floor price tends to promote positive skewness. From a practical perspective, the presence of a positive skewness can help policy design, in that a positive price asymmetry means that a minimum price level can be established confidently (Sadiq et al 2020). Similar findings were reported by Stigler (2011) and Sukati (2017).…”
Section: Resultssupporting
confidence: 78%
“…A ceiling price tends to promote negative skewness while a floor price tends to promote positive skewness. From a practical perspective, the presence of a positive skewness can help policy design, in that a positive price asymmetry means that a minimum price level can be established confidently (Sadiq et al 2020). Similar findings were reported by Stigler (2011) and Sukati (2017).…”
Section: Resultssupporting
confidence: 78%
“…It can be inferred that rice is a storable commodity thus exhibiting positive rather than negative skewness. Stigler (2011), Sukati (2017 and Sadiq et al (2020a) reported that floor prices tend to generate positive skewness whereas prices at the ceiling tend to encourage negative skewness. The existence of positive skewness from a realistic point of view will assist policy design in that positive price asymmetry means that one can be very secure in setting a minimum price level.…”
Section: Summary Statistics Of the Market Pricesmentioning
confidence: 99%
“…However, the residual was not normally skewed as evident by the Doornik-Hansen test statistic which is within the plausible margin of a 10% probability level. Non-normality has been reported not to be a serious problem as data in their natural form in most cases are not normally distributed (Sadiq et al, 2017(Sadiq et al, , 2020a. Thus, the model is reliable for prediction with certainty, efficiency, and consistency.…”
Section: Degree Of Market Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of an arbitrary current shock ( 𝛿) and history(𝜔 ) , the Generalized Impulse Response Function (GIRF) is as follows [20]- [23]:…”
Section: Model Specification: Impulse Response Functionsmentioning
confidence: 99%